Male sex hormones response after a month-long Himalayas trek in relation to hemoglobin oxygen saturation - Ružić, Lana (Array, 2018)
High-altitude tourism is becoming increasingly popular among non-athletic population, but its potential impact on health is often neglected. This study investigated the changes in male sex hormones after the trek at altitudes between 1400 m and 6476 m. Seventeen recreational lowland men (age 48±11 years) participated in a 26-day Himalayan trek, with the highest point reached being Mera Peak. The initial measurements were performed 10 days before departure and included blood tests (total testosterone, sex hormone-binding globulin – SHBG, dehydroepiandrosterone sulfate – DHEA-S, follicle stimulating hormone – FSH, and luteinizing hormone – LH) and ergometry on a treadmill. The final measurements were done 24 h after the return to 122 m (four days after reaching the altitude of 4300 m, and eight days after the altitude of 6476 m). During the tour, SpO2 and heart rate were measured 21 times. An increase in SHBG (42.6±10.6 to 50.7±12.0 nmol·L-1; p=.011), and subsequent decrease in calculated free testosterone (1.8±0.3 to 1.6±0.3%; p=.003) were observed. There was a significant correlation between the relative testosterone decrease and SHBG with mean SpO2 (Spearman R=-0.64 and 0.41, respectively). LH and FSH increased significantly (FSH Median/ IQR before=3.9/3.1-5.4 and after 4.6/4.0-7.1 IU·L-1; p=.001 and LH Median/IQR before=4.8/3.1-5.2 and after 5.9/4.9-9.3 IU·L-1; p=.008). The changes in LH and FSH did not correlate with SpO2, whereas the physical fitness levels (expressed in MET) did. The pituitary-adrenal-gonadal axis was affected by the altitude trek (involving physical exertion and hypoxia in combination), but the origin, duration and impact of changes in various aspects of men’s health should be further investigated.